Influence of the Support of Bimetallic Platinum Tungstate Catalysts on 1, 3‐Propanediol Formation from Glycerol. Issue 24 (29th November 2017) - García‐Fernández, Sara; Gandarias, Inaki; Tejido‐Núñez, Yaiza; Requies, Jesús; Arias, Pedro Luis
Abstract: Three aluminium oxide materials and a HZSM‐5 zeolite were used as supports of bimetallic Pt‐WO x catalysts to establish structure–activity relationships in the glycerol hydrogenolysis reaction. The surface W density and the intimate contact between Pt and WO x were key parameters. Surface W density controls the formation of polytungstates, the only species able to produce the weak Brønsted acidity that is required to produce 1, 3‐propanediol selectively. The comparison between the HZSM‐5 and the Al2 O3 supports demonstrated that an increment of the medium Brønsted acidity is detrimental for the selective 1, 3‐propanediol formation as it promotes reactions that yield 1‐propanol and propane. An increase of the dispersion of Pt on the Pt/WO x /Al2 O3 catalysts led to higher glycerol conversions but also promoted the hydrogenolysis routes that lead to 1, 2‐ and 1, 3‐propanediol similarly. On the contrary, an increase of the Pt metal content favoured the hydrogenolysis route that leads to 1, 3‐propanediol significantly. A more intimate contact between Pt and WO x promoted the hydrogenation of the intermediate carbocation, formed and stabilised on a polytungstate active site, into 1, 3‐propanediol. Abstract : The closer the better : Intimate contact between Pt and polytungstate sites favors the selective production of 1, 3‐propanediol. Weak Brønsted acidity is required, but an enhancement of medium Brønsted sites promotes the formation of 1‐propanol and propane through the acrolein route.